Circular economy: Current view from the construction industry based on published definitions - Curado, M. T.; Resende, R.; Rato, V. M. (Sustainability: Science, Practice and Policy, 2024)
The third decade of this millennium has seen a growing interest in using the circular economy (CE) concept to achieve the broad goals of sustainable development. Still, like the latter, the former notion has different meanings to different audiences in general and in the construction sector in particular. This Brief Report aims to assess how the construction sector regards the CE concept, or more precisely, how it defines it. This work draws on previous research by Kirchherr et al. (2017), applying their generic framework to the construction sector by dividing the CE into its main components and subcomponents and quantifying the extent of their acceptance. The main contribution of this work lies in establishing a benchmark for comparison with other industries and across time within the construction industry. We start with an analysis of the available literature and then focus on how the reviewed works perceive the scope of CE, its deployment systems, enablers, and its relationship with sustainable development. Our results confirm that the sector is embracing the linkage of CE to sustainable development while revealing a lesser concern for CE’s social and future dimensions. This Brief Report also shows that the understanding of CE actions in terms of a hierarchy is still limited. However, its three main components (Reduce, Reuse, Recycle) are almost universally espoused, with the Recover component is mentioned by just over half of the reviewed works.